2011
DOI: 10.1016/j.neuropharm.2010.11.026
|View full text |Cite
|
Sign up to set email alerts
|

HZ166, a novel GABAA receptor subtype-selective benzodiazepine site ligand, is antihyperalgesic in mouse models of inflammatory and neuropathic pain

Abstract: a b s t r a c tDiminished GABAergic and glycinergic inhibition in the spinal dorsal horn contributes significantly to chronic pain of different origins. Accordingly, pharmacological facilitation of GABAergic inhibition by spinal benzodiazepines (BDZs) has been shown to reverse pathological pain in animals as well as in human patients. Previous studies in GABA A receptor point-mutated mice have demonstrated that the spinal anti-hyperalgesic effect of classical BDZs is mainly mediated by GABA A receptors contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 29 publications
3
60
1
Order By: Relevance
“…Intrathecal benzodiazepines and neurosteroids have been shown precliincally in rodent models to attenuate tissue and nerve injury hyperpathic states [218,[222][223][224][225][226]. In dogs, intrathecal benzodiazepines have been shown to depress nociceptive reflexes [227].…”
Section: Spinal Gaba-a Activationmentioning
confidence: 99%
“…Intrathecal benzodiazepines and neurosteroids have been shown precliincally in rodent models to attenuate tissue and nerve injury hyperpathic states [218,[222][223][224][225][226]. In dogs, intrathecal benzodiazepines have been shown to depress nociceptive reflexes [227].…”
Section: Spinal Gaba-a Activationmentioning
confidence: 99%
“…Both questions were addressed with conditional GABA A R deficient mice (hoxb8-α2 À/À mice), which lack the GABA A R α2 subunit specifically from the spinal cord and dorsal root ganglia (DRGs) (up to about segment C4). In these experiments, a recently developed benzodiazepine site agonists (HZ166; Rivas et al, 2009) was employed which exerts antihyperalgesic actions similar to systemic diazepam but with reduced sedative and muscle relaxant properties (Di Lio et al, 2011). Antihyperalgesia was assessed as the change in heat and pin-prick induced withdrawal responses.…”
Section: Spinal Gaba a R Subtypes Mediating Antihyperalgesia: Evidencmentioning
confidence: 99%
“…Other benzodiazepines with low sedative propensities include HZ166 (Rivas et al, 2009) and TPA023 (Atack et al, 2006). HZ166, which exerts rather high intrinsic activity, was antihyperalgesic in inflammatory and neuropathic mouse models (Di Lio et al, 2011), while TPA023, which is a low intrinsic activity partial agonist, showed comparatively weak anti-allodynic or antihyperalgesic effects (Munro et al, 2011;Nickolls et al, 2011). Other compounds, which have higher intrinsic activities at α1-GABA A Rs than at α2-, α3-, and α5-GABA A Rs, did not exhibit antihyperalgesic activity at non-sedative doses.…”
Section: Antihyperalgesic Action Of Benzodiazepines With Improved Submentioning
confidence: 99%
“…Although other subtype-selective GABA A receptor modulators have since been reported to possess similar analgesic properties in rodent models of pathological pain (Di Lio et al, 2011;Nickolls et al, 2011;Munro et al, 2011) little was known at this time about the efficacy profile required to mediate preferential analgesia. In pursuit of this goal NS11394 was compared to other known positive allosteric modulators (PAMs) that included the nonselective full allosteric modulator diazepam, the GABA A -α1-selective modulator zolpidem, the partial nonselective modulator bretazenil and the α4 preferring agonist gaboxadol .…”
Section: Ns11394mentioning
confidence: 99%
“…However, the agents differ with respect to absolute efficacy at each subtype of GABA A receptor (e.g., even though most compounds have greater selectivity at GABA A α2 and/ or α3 receptors than at GABA A α1 receptors, they differ with respect to the level of efficacy at GABA A α1 receptors per se (see Munro et al, 2009 α3β3γ2 and α5β3γ2, respectively), Di Lio et al, 2011). In keeping with these specific facets, HZ166 displayed flumazenil-reversible anti-hyperalgesic efficacy in mice with zymosan A-induced inflammation and CCI induced mechanical hypersensitivity (Di Lio et al, 2011), (Table 1). Importantly, the efficacy obtained in chronic constriction injury mice was comparable to the standard of care compound gabapentin, and as shown previously for L-838,417 did not tolerate out with repeated administration.…”
Section: Ns11394mentioning
confidence: 99%